Business Bribery Risk Assessment - Stanley, Karlyn D. (RAND Corporation, 2014)
Businesses operating overseas have inadequate tools for assessing business bribery risk and their potential risk of violating various anti-corruption laws. This report introduces a new index, the TRACE Matrix, for business bribery risk assessment. The index provides a quick and useful guide for businesses operating overseas based on a conceptual model of bribery risk and supported by data specific to firms.